IMPLEMENTASI REPETITIVE METHOD DALAM MENINGKATKAN PEMAHAMAN SISWA MENGENAI MATERI PENDIDIKAN AGAMA ISLAM - Ahmad Syaddad; Siti Nurhayati (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
This research aims to determine the implementation of the repetitive method in improving the understanding of class IX B students of SMP Negeri 1 Teluk Bayur towards Islamic Religious Education (PAI) material. The repetitive method is a learning strategy that emphasizes the repetition of material in a structured and consistent manner, with the aim of strengthening students' memory and understanding. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results showed that the repetitive method was effective in improving students' understanding of PAI material. Supporting factors include student motivation, teacher support, and adequate learning facilities. Inhibiting factors include time constraints, lack of student participation, and less than optimal family support.